2008
DOI: 10.1017/s1461145707008401
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in psychiatric disorders: evidence base and therapeutic implications

Abstract: Oxidative stress has been implicated in the pathogenesis of diverse disease states, and may be a common pathogenic mechanism underlying many major psychiatric disorders, as the brain has comparatively greater vulnerability to oxidative damage. This review aims to examine the current evidence for the role of oxidative stress in psychiatric disorders, and its academic and clinical implications. A literature search was conducted using the Medline, Pubmed, PsycINFO, CINAHL PLUS, BIOSIS Previews, and Cochrane datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
569
4
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 878 publications
(624 citation statements)
references
References 191 publications
(267 reference statements)
20
569
4
14
Order By: Relevance
“…A recent finding also suggested that trans-unsaturated fatty acids have a dose-response effect on clinical depression (48) . Therefore, the intake of special nutrients is often considered a mediator of the association between whole diet and mental problems (49)(50)(51)(52) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent finding also suggested that trans-unsaturated fatty acids have a dose-response effect on clinical depression (48) . Therefore, the intake of special nutrients is often considered a mediator of the association between whole diet and mental problems (49)(50)(51)(52) .…”
Section: Discussionmentioning
confidence: 99%
“…Para revisões sistemáticas recentemente publicadas com descrições mais detalhadas dos estudos, sugerimos os trabalhos de Grande et al 27 , em relação a neurotrofinas, de Goldstein et al 16 e de Drexhage et al 28 , para inflamação. Há revisões que abordam em profundidade a relação entre biologia oxidativa e transtorno bipolar 2,29,30 .…”
Section: Métodounclassified
“…Refletindo o interesse no estresse oxidativo, o volume de trabalhos publicados sobre esse tema em psiquiatria tem crescido exponencialmente 29 . Isso provavelmente se deve à ênfase dada nos últimos anos, na neuropsiquiatria, à sensibilidade cerebral ao dano oxidativo.…”
Section: Estresse Oxidativounclassified
See 1 more Smart Citation
“…cognitivedysfunction 3 .Recently, oxidative stress has been proposed as a contributing factor in the pathogenesis of depression 4 .Again, significantly lower plasma concentrations of several key antioxidants (vitamin-E,zinc and coenzyme Q),as wellas lower antioxidant enzyme activity, have been reported in major depression 5 .Depression is aneuropsychiatric illness that has been estimated to be third among the global burden of diseases 6 .…”
Section: Introductionmentioning
confidence: 99%